TAPPING BOX APPLICATION, QUALITY SERVICE, TAX KNOWLEDGE, TAX PAYER’S OBEDIENCE WITH TAX PENALTY AS MODERATING VARIABLE - Rasmini, Ni Ketut; Mimba, Sri Harta (Jurnal Ekonomi Kuantitatif Terapan, 2021)
This Research aims to test the impact of tapping box application, service quality, and tax knowledge on the obedience of Hotel and Restaurant tax payer with tax penalty as moderating variable at Badan Pendapatan Daerah in Denpasar. This research conducted on all Hotels and Restaurants that have tapping box application in Denpasar (141 units). Data was collected using survey method and only 100 questioners used in this research. Data was tested using moderated regression analysis. The result showed that the application of tapping box, service quality, and tax knowledge have positive impact on the obedience of Hotel and Restaurant Tax payer. Tax penalty stronger the impact of the application of tapping box, service quality, and tax knowledge on the obedience of Hotel and Restaurant Tax payer. This research give contribution about the importance of tapping box application, provided good services, knowledge about local tax, and tax penalty that could improve obedience of tax payer.